A Comprehensive Flexural Analysis for Sustainable Concrete Structure Reinforced by Embedded Parts - Yuantian Sun; Junfei Zhang; Yunchao Tang; Yufei Wang; Junbo Sun; Xiangyu Wang (Advances in Civil Engineering)
In this research, the plate embedded parts and grooved embedded parts reinforced concrete structures were investigated. Two types of plate embedded parts and three types of grooved embedded parts experienced coating treatment to enable sustainable function. Later, the ultimate failure capacity by bending experiments was conducted and compared with the theoretically calculated results. Moreover, three grooved embedded parts were simulated by ABAQUS to compare the results with the experimental exploration results, which was in close agreement with the theoretically calculated results and finite element analysis results. The result indicated that the failure modes of the embedded specimens under the five working conditions are all concrete vertebral failure. The plate-type embedded components were proved to exhibit higher ultimate bearing capacity than the grooved embedded parts. Moreover, the flexural and shear capacity of these five types of embedded parts has not been fully developed. The ultimate flexural and shear capacity of these five types of embedded parts could be further explored by adjusting the higher concrete grade.